Actin-Capping Protein and the Hippo pathway regulate F-actin and tissue growth in Drosophila - Fernández, B.G. (2011)
The conserved Hippo tumor suppressor pathway is a key kinase cascade that controls tissue growth by regulating the nuclear import and activity of the transcription co-activator Yorkie. Here, we report that the actin-Capping Protein αβ heterodimer, which regulates actin polymerization, also functions to suppress inappropriate tissue growth by inhibiting Yorkie activity. Loss of Capping Protein activity results in abnormal accumulation of apical F-actin, reduced Hippo pathway activity and the ectopic expression of several Yorkie target genes that promote cell survival and proliferation. Reduction of two other actin-regulatory proteins, Cofilin and the cyclase-associated protein Capulet, cause abnormal F-actin accumulation, but only the loss of Capulet, like that of Capping Protein, induces ectopic Yorkie activity. Interestingly, F-actin also accumulates abnormally when Hippo pathway activity is reduced or abolished, independently of Yorkie activity, whereas overexpression of the Hippo pathway component expanded can partially reverse the abnormal accumulation of F-actin in cells depleted for Capping Protein. Taken together, these findings indicate a novel interplay between Hippo pathway activity and actin filament dynamics that is essential for normal growth control.